STRATEGI PENGEMBANGAN UMKM INDUSTRI PERDAGANGAN DI KAWASAN KECAMATAN BONTANG SELATAN BERDASARKAN PERSEPSI PELAKU UMKM: Lokasi Studi Kecamatan Bontang Selatan - Septian Imandi Krisdianto; Achmad Ghozali (Jurnal PROYEKSI: Arsitektur dan Perencanaan, 2022)
MSMEs in Bontang City from 2019 to 2020 have quite a large number of MSME actors. However, PAD in Bontang City has decreased. Bontang City's GRDP growth rate for the MSME sector has also continued to decline. The purpose of this study is to provide suggestions for the development strategy of the trading industry SMEs in South Bontang District to increase the GRDP growth rate of the MSME sector, with the goal being carried out to achieve the goal of identifying the distribution of the characteristics of the trading industry SMEs in each sub-district in Bontang City, analyzing priority factors for the development of SMEs trade industry, and formulate the right strategy for the development of SMEs in the trade industry in South Bontang District. The analytical method used is a Likert scale/scoring analysis to determine the factors of MSME development. The results obtained based on the priority factors obtained are internal factors in which there is human resource expertise which is a priority factor for the development of SMEs in the trading industry. The strategy formulated based on the results of the analysis is to increase human resource expertise, develop the potential of the fashion business in the Berbas Pantai Village, develop the potential for the furniture business in the Tanjung Laut Indah Village, maintain stability and increase the food and beverage and craft businesses, and provide financial assistance and facilities for production.